Pengaruh Metode Promosi Kesehatan Tentang Nyeri Punggung Bawah Terhadap Perubahan Sikap Kerja Di Tempat Pelelangan Ikan Pemalang - Widodo, Slamet, Totok Budi Santoso , S.Fis , MPH, Isnaini Herawati, SSt. FT, M. Sc (2016)
Background: One of the factors of low back pain (LBP) experienced worker is working attitude that causes the body's natural not moved against the natural or adoptive-transport activities manually backs are bent, twisted body. Another factor that is a working tool and a work station that is not in accordance with the capabilities and limitations of the workers will trigger the occurrence of musculoskeletal complaints Objective: This study was conducted to determine the effect of health promotion methods on lower back pain attitude towards work at the fish auction pemalang. Benefits Research: For information on workers at the fish auction that work is being undertaken potentially lead to musculoskeletal disorders, one of which is lower back pain so that workers can anticipate and take steps to prevent as well as improvements in the workplace. Methods: This research uses quasi-experimental approach, with a design in the form of pre and post test two groups design. The sampling technique used purposive sampling, as many as 57 respondents. Measuring instrument research using questionnaire. The statistical test used was Wilcoxon test and test the effect of different test mann Whitney influence. Results: Statistically influence health promotion LBP risk level by working attitude leaflet showed a p-value of 0.009 or proba bility (significance) <0.05. To work attitude lecture shows the p-value of 0.001 or probability (significance)> 0.05. Conclusion: There is a positive influence on the attitudes of health promotion work for workers at the fish auction (TPI) Limbangan village of Pemalang methods leaflets and talks but the effect is greate r health promotion lecture.